2019
DOI: 10.1016/j.ssmph.2019.100495
|View full text |Cite
|
Sign up to set email alerts
|

Association between unintended births and risk of postpartum depression: Evidence from Ethiopia, India, Peru and Vietnam

Abstract: Previous studies have shown that unintended births adversely affect birth outcomes, child health and cognitive development in developing countries. However, only a few studies have examined the association between unintended births and risk of postpartum depression (PPD) in these countries. The study uses data from the first wave of Young Lives Study (YLS) conducted in 2002 in Ethiopia, India, Peru and Vietnam to examine the association between birth intention and the risk of PPD. Bivariate and multivariable l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…We see here a link between employment and financial security, with its potential impact on the children of single mothers. This phenomenon is not exclusive to Vietnam (UN, 2010), as it has also recently been reported by studies in India and Peru and Ethiopia (Upadhyay et al , 2019).…”
Section: Analysis and Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…We see here a link between employment and financial security, with its potential impact on the children of single mothers. This phenomenon is not exclusive to Vietnam (UN, 2010), as it has also recently been reported by studies in India and Peru and Ethiopia (Upadhyay et al , 2019).…”
Section: Analysis and Discussionsupporting
confidence: 58%
“…In Vietnam, for instance, single motherhood is generally a source of unhealthy psychological state for women (Tho Tran et al , 2018). The phenomenon of single motherhood calls for further investigation in terms of understanding its occurrence (Upadhyay et al , 2019) and impact. Tho Tran et al (2018), owing to the close relationship it has with societal norms and cultural consequences (Hofstede, 2018) especially, around the psychological state of single mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with suspected PPD in multivariate analysis were unintended pregnancy, low satisfaction with childbirth, and depression during pregnancy. Previous studies reported that unintended pregnancy is associated with PPD [ 23 , 24 ]. A prospective study in South Korea showed that unintended pregnancy contributed to PPD and parenting stress in mothers through marital conflict and low father’s participation in child care [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, infant characteristics like adverse birth and infant health outcomes (22), di cult temperament(23) and unwanted gender (24) are risk factors. Mothers with poor physical health (25), poor obstetric histories(26), unplanned pregnancy (27), and a history of psychiatric illness (28) are likely to have PND. Moreover, poor environmental conditions (29) and cultural practices (30), (31) are also PND predictors.…”
Section: Introductionmentioning
confidence: 99%